Sedimentological interpretation of an Ediacaran delta: Bonney Sandstone, South Australia. Issue 3 (2nd April 2016) - Counts, J. W.; Rarity, F.; Ainsworth, R. B.; Amos, K. J.; Lane, T.; Morón, S.; Trainor, J.; Valenti, C.; Nanson, R.
ABSTRACT: The type section of the late Ediacaran ( ca 565 Ma) Bonney Sandstone in South Australia provides an opportunity to interpret a succession of Precambrian clastic sediments using physical sedimentary structures, lithologies and stacking patterns. Facies models, sequence stratigraphic analysis, and process-based architectural classification of depositional elements were used to interpret depositional environments for a series of disconformity-bounded intervals. This study is the first detailed published work on the Bonney Sandstone, and provides additional context for other Wilpena Group sediments, including the overlying Rawnsley Quartzite and its early metazoan fossils. Results show that the ∼300 m-thick section studied here shows a progressive change from shallow marine to fluvially dominated sediments, having been deposited in storm-dominated shelf and lower shoreface environments, lower in the section, and consisting primarily of stacked channel sands, in a proximal deltaic environment near the top. Based on the degree of influence of wave, tidal or fluvial depositional processes, shallow marine sediments can be classified into beach, mouth bar, delta lobe and channel depositional elements, which can be used to assist in predicting sandbody geometries when only limited information is available. Sediments are contained within a hierarchical series of regressive, coarsening-upward sequences, which are in turn part of a larger basin-scale sequence that likely reflects normal regression and filling of accommodation throughout a highstand systems tract. Paleogeographic reconstructions suggest the area was part of a fluvially dominated clastic shoreline; this is consistent with previous reconstructions that indicate the area was on the western edge of the basin adjacent to the landward Gawler Craton. This research fills in a knowledge gap in the depositional history of a prominent unit in the Adelaide Rift Complex and is a case study in the interpretation of ancient deposits that are limited in extent or lacking diagnostic features.